Implementasi dan Implikasi Peraturan Daerah Kabupaten Sampang Nomor 7 Tahun 2019 tentang Madrasah Diniyah Takmiliyah - Ismail, Ismail; Zainullah, Zainullah; Tamam, Nurul (Jurnal Review Politik, 2022)
This study refers to qualitative research methods, the data analysis was carried out by means of data reduction, data presentation, and verification and drawing conclusions. This research resulted in: (1) Implementation of this regional regulation in the form of: (a) Provision of Assistance for Organizing Diniyah Education and Private Teachers (BPPDGS); (b) Madrasah diniyah stakeholder synergy; and (c) Community Involvement in Strategic Policy Formulation; (2) This regional regulation has implications for madrasah diniyah in the form of: (a) institutional strengthening; (b) improving the quality of learning processes and outcomes; and (c) to become an instrument for realizing the vision and mission of the Sampang government "Sampang Hebat Bermartabat". Penelitian tentang implementasi dan implikasi perda Kabupaten Sampang No 7 tahun 2019 tentang Madrasah Diniyah Takmiliyah mengacu pada metode penelitian kualitatif, analisis data dilakukan dengan cara reduksi data, penyajian data, dan verifikasi dan penarikan kesimpulan. Penelitian ini menghasilkan: (1) Implementasi kebijakan perda ini dalam bentuk: (a) Pemberian Bantuan Penyelenggaraan Pendidikan Diniyah dan Guru Swasta (BPPDGS); (b) Sinergi stake holders madrasah diniyah; dan (c) Keterlibatan Masyarakat dalam Perumusan Kebijakan Strategis; (2) Perda ini berimplikasi terhadap madrasah diniyah dalam bentuk: (a) penguatan institusi; (b) peningkatan kualitas proses dan hasil pembelajaran; dan (c) menjadi instrumen perwujudan visi misi pemerintah Kabupaten Sampang “Sampang Hebat Bermartabat”